2020
DOI: 10.1080/17483107.2020.1854874
|View full text |Cite
|
Sign up to set email alerts
|

Assistive technologies, educational engagement and psychosocial outcomes among students with disabilities in higher education

Abstract: Purpose: Increasing numbers of students with disabilities are accessing higher education each year, yet little is known about their assistive technology (AT) needs and its influence on relevant outcomes. The aim of this study was to examine met/unmet AT needs on educational engagement, academic self-efficacy and well-being and the impact of AT use in the areas of competence, adaptability and self-esteem for students with disabilities in higher education in Ireland. Methods: One hundred and eleven students with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 52 publications
0
11
0
2
Order By: Relevance
“…The importance of assistive technologies (AT) in supporting students with disabilities in higher education further illustrates the broad impact of technology on learning outcomes. McNicholl, Desmond, and Gallagher (2023) demonstrate that AT use supports educational engagement, increases well-being and academic self-efficacy, and positively impacts competence, adaptability, and self-esteem. These findings highlight the critical role of AT in ensuring equitable access to education and supporting diverse learner needs, thereby enhancing learning outcomes for students with disabilities.…”
Section: Learning Outcomes In Higher Educationmentioning
confidence: 83%
See 2 more Smart Citations
“…The importance of assistive technologies (AT) in supporting students with disabilities in higher education further illustrates the broad impact of technology on learning outcomes. McNicholl, Desmond, and Gallagher (2023) demonstrate that AT use supports educational engagement, increases well-being and academic self-efficacy, and positively impacts competence, adaptability, and self-esteem. These findings highlight the critical role of AT in ensuring equitable access to education and supporting diverse learner needs, thereby enhancing learning outcomes for students with disabilities.…”
Section: Learning Outcomes In Higher Educationmentioning
confidence: 83%
“…Moreover, the importance of assistive technologies (AT) in supporting students with disabilities in higher education cannot be overstated. McNicholl, Desmond, and Gallagher (2023) found that AT use not only supports educational engagement but also increases well-being, academic self-efficacy, and has a positive impact on competence, adaptability, and self-esteem. This research highlights the critical role of AT in ensuring equitable access to education and supporting diverse learner needs.…”
Section: Introduction Relevance Of Educational Technologymentioning
confidence: 94%
See 1 more Smart Citation
“…Debemos tener en cuenta que esta falta de accesibilidad a dichos recursos puede constituir además un elemento de segregación, aumentar la brecha digital o la exclusión social (Zubillaga del Río, 2010). Es necesario, por tanto, tener en cuenta cómo adaptar el currículo para este alumnado (Lorenzo, Lledó, Arraez, Lorenzo-Lledó & Gómez Puerta, 2017), ya que no sólo se deben utilizar estar herramientas para realizar trabajos o para comunicarse, sino que también deben servir como apoyo y permitir la accesibilidad del alumnado (Pastor & Zubillaga del Río, 2012) para favorecer su bienestar y autoestima (McNicholl, Desmond & Gallagher, 2020), así como, para brindar la igualdad de oportunidades de los estudiantes (Kurt et al, 2016).…”
Section: Discussionunclassified
“…Its main goal is to enhance the wellbeing of an individual by increasing the autonomy level within the daily life context. The use of these products is aimed not only to increase a specific functional ability but also to enhance the users' social inclusion [1]. However, the innovation of these products is mainly driven by technology, ergonomics, and their technical feasibility, resulting in a limited users' engagement during the design process.…”
Section: Introductionmentioning
confidence: 99%